Long run macroeconomic determinants of remittance flows to Jamaica 1983-1999 - McLeod, Georgia...[et al.] (Caribbean Centre for Monetary Studies [St. Augustine]TT, 2003)
Seeks to determine the long run relationship between remittances and various factors in both the home and major host countries viz. United States, Britain and Canada.